The Procurement, Property and Supply Sections of the Lung Center of the Philippines - Aban, Carmelita H.; Bukas, Carina F.; Restituto, Perla Selina A.; Rubido, Trudy M.; Tarrayo, Romeo Carmelo G. Jr (College of Engineering, 1988)
Lung Center of the Philippines (LCP) is a tertiary level care center specializing in the treatment of care and research of lung and allied diseases. In its 6 years of operations it has continually concerned itself with providing quality patient care on a national level specifically for those afflicted with lung problems. To achieve this end, supplies are constantly purchased, distributed to the end-users which consist of all sections of the LDP, both in Medical and Administrative Service Systems. Such is the main function of the Procurement, Property and Supply Sections (PPSS) of the LCP whose information system is the one under study.